Insect Pathogens: Molecular Approaches and Techniques - Stock, S. Patricia (CABI, 2014)
Like other natural enemies, insect pathogens, including bacteria, viruses, fungi, protozoa and nematodes, have demonstrated to be environmentally safe and economical alternatives for control of a wide range of arthropod pests. Because of their documented efficacy and the advantages they offer in comparison with chemical pesticides, interest in these organisms has increased exponentially over the past decades. Furthermore, their ability to reduce insect populations has also been the compelling force to further investigate their biology, physiology, ecology and molecular biology. In this respect, molecular technology has played a crucial role in many aspects related with the field of insect pathology, leading to the development of methods and techniques that have had an impact on both basic and applied research beyond the scope of insect pathology. In this book, we have attempted to bring together a broad array of molecular techniques and approaches currently used in insect pathology. We hope to facilitate their consideration, development and success by a wide audience including students, educators and scientists in academic, private and governmental sectors. This book is divided into four parts: (i) Identification and Diagnostics; (ii) Evolutionary Relationships and Population Genetics; (iii) Host–Pathogen Interactions; and (iv) Genomics and Genetic Engineering. Sixteen chapters have been written by leading researchers in the field which provide comprehensive and up-to-date information on each part